A brush with death : an artist in the death camps - Wyszogrod, Morris, 1920- (SUNY series in modern Jewish literature and culture., 1999)
"In this memoir Morris Wyszogrod recounts his experiences from the time of the Nazi invasion of Poland to the liberation of the Theresienstadt concentration camp."